Impact of Frontline Demonstration on Indian Mustard through Improved Technology - Shishir Kumar* Yogesh Chandra Srivastava and Ameesh John Stephen, (Indian Journal of Extension Education, 2018)
Indian mustard (Brassica juncea L.) is a major oilseed crop of Uttar Pradesh. It is also one of the importantoilseed crops of Eastern Uttar Pradesh. However, its productivity is very low in the district of eastern UttarPradesh compared to other districts of Uttar Pradesh. The Directorate of Extension SHIATS, Allahabad hascarried out 21 frontline demonstrations on Indian mustard covering an area of 7 ha. of farmers field in 7districts (Allahabad, Kaushambi, Fatehpur, Pratapgarh, Mirzapur, Sonebhadra & Bhadohi) in 2015 & 2016to exhibit latest production technologies and compared it with farmer’s practice. An attempt has also beenmade to know the productivity of frontline demonstrations and the adoption of latest production technologiesby the 21 FLD farmers and 21 non-FLD farmers. FLD farmers and non FLD farmers were randomly selectedfrom FLD villages. The results were compared between FLD plots and control plots. The results revealed thatimproved technologies of mustard enhanced yield from 14.32q/ha to 18.62 q/ha in frontline demonstrations.The percentage of increase in yield ranges from 17.77 to 31.14. The extension gap and technology gap wererecorded ranging between 2.68-3.77 q/ha and 1.38-5.68 q/ha, respectively. The technology index rangedfrom 6.90 % to 22.40 %. The results indicated that the FLD was effective in changing attitude, knowledge andadoption of improved technologies of mustard and ultimately in obtaining sustain income.